Building Reliable Large-Scale Distributed Systems: When Theory Meets Practice - Zhou, Lidong (Column 35, SIGACT News, 2009)
In a follow-up on the theme of the previous Distributed Computing Column (SIGACT News 40(2), June 2009, pp. 67–95), which dealt with “Cloud Computing”, the current column deals with the tension between theoretical results and practical deployments of large-scale distributed systems. It consists of a single contribution by Lidong Zhou of Microsoft Research Asia, who has experience on both sides of this divide– both in designing distributed algorithms and in building large-scale distributed systems. Many thanks to Lidong for his contribution.